Regional Laws and Policies in Encouraging Community Participation for Sustainable Environmental Management - Moh. Taufik; Sugiyanto Sugiyanto; Soesi Idayanti; Sanusi Sanusi; Moh. Wildan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Global studies have demonstrated that when communities are involved from the early stages of environmental planning and management, they become better prepared to cope with the risks associated with climate change and environmental degradation. For instance, World Bank reports emphasize that community engagement enhances local resilience and supports sustainable development. This finding indicates that public participation is not merely a supplementary component but rather a fundamental element in establishing effective, equitable, and sustainable environmental policies. In practice, however, the implementation of participation-based policies at the regional level is not always straightforward. Numerous challenges persist, including limited access to information, insufficient technical capacity among community members to engage in environmental issues, inequalities within deliberative processes, and the influence of local political dynamics. Several international studies have also noted that participation may become ineffective when communities are involved merely as a procedural formality without meaningful opportunities to influence decision-making processes. This study focuses on analyzing legal instruments and strategic measures adopted by regional governments to mobilize citizen participation in long-term environmental conservation. The research is categorized as library research. The analysis of the literature is conducted using a theoretical legal approach, commonly referred to as normative juridical analysis. The findings indicate that regional policies have the potential to transform public participation from a mere formality into genuine engagement that significantly influences environmental management decisions. Broad public involvement following the Constitutional Court Decision No. 91/PUU-XVIII/2020 concerning the Job Creation Law is expected to enhance oversight of the effectiveness of amendments to previously established conservation provisions. This aspect reflects the practical role of communities in environmental protection. Therefore, systemic reforms aimed at standardizing and optimizing Environmental Impact Assessment (EIA/AMDAL) instruments require strong support from various sectors of society.